Did prudent risk management practices or weak consumer demand reduce Paycheck Protection Program lending by the largest banks? - Paul H. Kupiec (American Enterprise Institute (AEI), 2020)
Analysis of data on bank-specific average PPP loan size produces results that are inconsistent with a loan demand explanation. Absent good measures of PPP loan demand, the source of the observed differences in bank PPP loan activity cannot be definitively identified using bank regulatory data alone.
Keywords: A; 330; Banks; Coronavirus; Fiscal Stimulus; Risk; US Economy